ROLE OF AGNIKARMA THERAPY IN THE MANAGEMENT OF KADARA (CORN): A CASE REPORT - M. Borkar, Kanchan; V. Shekokar, Anantkumar (International Journal of Ayurveda and Pharma Research, 2015)
Kadara (corn) is initially painless in condition but with its progress, it may become painful. In modern science, corn is being treated by using anti inflammatory drugs, corn cap, saliciylic acid and excision. Even today there is no satisfactory and permanent treatment available for corn because of its high recurrence tendency. According to Ayurveda, ˜Kadara can be correlated with the condition of corn. Aacharya Sushrut has advised Agnikarma (cauterization) for Kadara. Hence, in this study corn (Kadara) was treated by Agnikarma with Panchadhatu Shalaka (instrument made of 5 metals) in a systematic manner for a duration of 15 days with intervals of 5 days in 3 sittings. Here, we have applied two types of Agnikarma. i.e. Pratisaran (flat type of cauterization) and Bindu (dotted type of cauterization) which were used in combination with application of Tilatailam (sesame oil) for better results. This combination therapy provided cured management, which is observed in the present case study. The patient was followed upto 6 months for observation of recurrence.